2001
DOI: 10.1159/000051664
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy Improves the Recovery of the Skin Barrier Function: An Experimental Model Using a Contact Allergy Patch Test Combined with TEWL Measurements

Abstract: Background: Nickel (Ni) allergic contact dermatitis (ACD) alters the skin barrier. Objective: Our aim was to compare the efficacy of combination therapies on ACD, using a topical corticosteroid and a corneotherapy agent (barrier cream), with that of a single therapy with corticosteroids. Methods: On day 1, 3 Ni test patches were applied on each forearm of 14 Ni-patch-test-positive females. Four contained 5% Ni and 2 physiological saline. Either topical corticosteroid or barrier cream were matched with the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…Thus, a suppressive effect of topical steroid on the synthesis of intercellular lipids and keratohyalin-derived natural moisturizing factors might have been responsible for the decreased water-holding function of the SC after the treatment with betamethasone-17-valerate ointment. Moreover, Hachem et al [15]reported that combination of a topical corticosteroid with a corneotherapy agent (barrier cream) prevented the delay in the healing process of skin barrier disruption due to allergic contact dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a suppressive effect of topical steroid on the synthesis of intercellular lipids and keratohyalin-derived natural moisturizing factors might have been responsible for the decreased water-holding function of the SC after the treatment with betamethasone-17-valerate ointment. Moreover, Hachem et al [15]reported that combination of a topical corticosteroid with a corneotherapy agent (barrier cream) prevented the delay in the healing process of skin barrier disruption due to allergic contact dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, potential novel indications of FP corresponding to the beneficial effect on skin barrier disruption caused by nickelinduced allergic contact dermatitis come to horizon [66,67]. Studies about FP are accumulating, and results suggest an increased overall therapeutic potential in terms of efficacy and tolerability due to its increased affinity and improved GR pharmacokinetics.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo methods in humans are mostly based on assessment of the reduction either of a known contact sensitisation or of irritant and inflammatory changes in the skin when a barrier cream or moisturiser is used before application of the irritant [20,26,47,50,56] or allergen [28,45] in relation to an area of skin that was not pre-treated . Over the past years, this irritation test was modified by duration [56,57], concurrent application of two irritants instead of one [58], the use of a set of four standard irritants [19] or by change of the test area, e.g.…”
Section: Test and Evaluation Methodsmentioning
confidence: 99%
“…of a paper, which had already been published 4 years ago [53], is almost impossible. With regard to aspects of safety, allergic reactions to contents of skin protective creams, such as preservatives, might also play a role [27], but it is unclear if the various in vitro and in vivo methods [10,15,19,20,21,22,26,28,31,36,37,39,40,45,47,50,51,56,57,58,59,61] used are suitable to simulate real workplace conditions and whether these test results can be related to a real occupational exposure. With regard to aspects of safety, allergic reactions to contents of skin protective creams, such as preservatives, might also play a role [27], but it is unclear if the various in vitro and in vivo methods [10,15,19,20,21,22,26,28,31,36,37,39,40,45,47,50,51,56,57,58,…”
Section: Clinical Trialsmentioning
confidence: 99%